Antibacterial Activity of Crude Extract Red Algae Eucheuma spinosum Against Staphylococcus epidermidis Bacteria Growth - Nindhita Yusvantika; Rahayu Kusdarwati; Laksmi Sulmartiwi (Universitas Airlangga, 2022)
The use of seaweed (Eucheuma spinosum) as a source of bioactive ingredients from algae has not been widely carried out, even though it has secondary metabolites that are thought to have antibacterial activity. The purpose of this study was to determine the inhibitory activity of the crude extract of red algae E. spinosum on the growth of Staphyloccus epidermidis bacteria in vitro. The working method used is an experimental and qualitative research design. Extraction of E. spinosum used maceration with 96% ethanol solvent and evaporated using a rotary evaporator to obtain a crude extract yield of 1.54%. The phytochemical screening test used thin layer chromatography and precipitation tests. The results of phytochemical screening showed that crude extract of Eucheuma spinosum contained alkaloids, flavonoids, terpenoids and saponins. These compounds are thought to have the potential to have antibacterial activity. The antibacterial test was based on a comparative study of the literature using the disc diffusion method (Kirby-Bauer test) with a positive control of Clindamycin 10μl/ml and a negative control of distilled water. Comparison of the literature on the results of the antibacterial activity test is thought to be effective for treating acne-causing bacteria, namely Staphylococcus epidermidis with an average inhibition of 26.5 mm (30 μl). The antibacterial activity is because seaweed contains secondary metabolites such as flavonoids, alkaloids, terpenoids, and saponins. The need for herbal therapy to treat diseases caused by Staphylococcus epidermidis bacteria to reduce bacterial resistance to antibiotics.